Effect of overreaching on cognitive performance and related cardiac autonomic control - Dupuy, O.; Lussier, M.; Fraser, S.; Bherer, L.; Audiffren, M.; Bosquet, L. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to characterize the effect of a 2-week overload period immediately followed by a 1-week taper period on different cognitive processes including executive and nonexecutive functions, and related heart rate variability. Eleven male endurance athletes increased their usual training volume by 100% for 2 weeks, and decreased it by 50% for 1 week. A maximal graded test, a constant speed test at 85% of peak treadmill speed, and a Stroop task with the measurement of heart rate variability were performed at each period. All participants were considered as overreached. We found a moderate increase in the overall reaction time to the three conditions of the Stroop task after the overload period (816 ± 83 vs 892 ± 117 ms, P = 0.03) followed by a return to baseline after the taper period (820 ± 119 ms, P = 0.013). We found no association between cognitive performance and cardiac parasympathetic control at baseline, and no association between changes in these measures. Our findings clearly underscore the relevance of cognitive performance in the monitoring of overreaching in endurance athletes. However, contrary to our hypothesis, we did not find any relationship between executive performance and cardiac parasympathetic control.